MANAGEMENT OF DA'WAH LEARNING DEVELOPMENT IN THE ISLAMIC BROADCASTING COMMUNICATION STUDY PROGRAM AT MAKASSAR MUHAMMADIYAH UNIVERSITY. - takim, Mustakim (Universitas Islam Negeri Alauddin Makassar, 2023)
Mustakim, 2023. Management of Da'wah Learning Development in the Islamic Broadcasting Communication Study Program at Muhammadiyah University of Makassar This study examines the management of the development of da'wah learning in the Islamic Broadcasting Communication Studies program at the Muhammadiyah University of Makassar. Relevant literature is also presented in this study. With the following Problem Formulation: 1. Providing new information about the concept of preaching (dakwah) learning in the Islamic Broadcasting Communication Study Program at Muhammadiyah University Makassar. 2. Analyzing how the implementation of management in the development of preaching learning is carried out in the Islamic Broadcasting Communication Study Program at Muhammadiyah University Makassar. 3. Analyzing the supporting and inhibiting factors in the management of the development of preaching learning in the Islamic Broadcasting Communication Study Program at Muhammadiyah University Makassar.